65 Patients' and carers' perspectives on the use of the prognosis in palliative care scales (PiPS) predictor models: a qualitative study. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Spencer, Karen; Kalpakidou, Anastasia; Stone, Patrick; Todd, Chris; Keeley, Vaughan; Omar, Rumana; Vickerstaff, Victoria; Finlay, Dori-Anne; Buckle, Peter; Griffiths, Jane
Abstract : Background: Patients with advanced cancer and their carers often wish to know how long they have left to live, yet clinicians predictions of survival are often inaccurate and over-optimistic. The PiPS models use objective clinical data to predict whether palliative cancer patients will die within 'days', 'weeks' or 'months'. A previous study has shown that the PiPS models are at least as good as or more accurate than, clinicians'predictions of survival. We are currently validating the latter models in a large clinical study of palliative cancer patients (n=1884), this paper presents data from a nested qualitative study that explored patients'with advanced cancer and their carers'perspectives of the PiPS predictor models. Methods: We recruited a purposive sample of patients (n=29) and carers (n=20) from a hospice inpatient unit and a hospital day care unit. Patients and carers were asked about their preferences for prognostic information, preferred way of communicating life expectancy and acceptability of the PiPS models. Results: The majority of participants expressed desire for detailed prognostic information. Participants'preferences were influenced by patient age, time since diagnosis and coping ability. Most agreed that having life expectancy presented as days, weeks or months was the most meaningful. All considered the PiPS models acceptable for use in clinical practice and a useful tool in helping clinicians more accurately predict life expectancy. Conclusion: This study has highlighted that palliative care patients and carers wish to discuss accurate prognostication with clinicians. Our study further demonstrates the acceptability of the PiPS models to palliative care patients and their carers.